2010
DOI: 10.1099/ijs.0.018945-0
|View full text |Cite
|
Sign up to set email alerts
|

Stakelama pacifica gen. nov., sp. nov., a new member of the family Sphingomonadaceae isolated from the Pacific Ocean

Abstract: Stakelama pacifica gen. nov., sp. nov., a new member of the family Sphingomonadaceae isolated from the Pacific Ocean Strain JLT832 T was isolated from the surface of the Pacific Ocean at 174 u 21.709 E 20 u 34.449 N and formed a deep branch within the family Sphingomonadaceae. In this study, we characterized strain JLT832T by using a polyphasic approach. Strain JLT832T was initially isolated with seawater medium (SW) containing (per litre seawater filtered by 0.2 mm film) 1 g peptone, 1 g yeast extract, 20 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Since fatty acid profile analysis has played a central role in the pioneering taxonomic studies of the family Sphingomonadaceae (Busse et al, 1999;Takeuchi et al, 2001;Yabuuchi et al, 2002), besides the most closely related type strains shown in Table 1, all type species of closely related genera were involved in our comparative analysis (Table 2). In members of the family Sphingomonadaceae, C 18 : 1 v7c is the characteristic predominant fatty acid and the presence of 2-hydroxy fatty acids, mainly C 14 : 0 2-OH, is common, while C 17 : 1 v6c is usually present in lower amounts or is even absent (Busse et al, 1999;Takeuchi et al, 2001;Maruyama et al, 2006;Huang et al, 2009;Chen et al, 2010;Liang & Lloyd-Jones, 2010;Kämpfer et al, 2012;Uchida et al, 2012). This latter compound was found in high amounts in ERB1-3 T (29.2 %) compared with the most closely related type strains, and in ERB1-3 T , C 15 : 0 2-OH was another characteristic hydroxy fatty acid (representing .5 %).…”
Section: Cells Of Strain Erb1-3mentioning
confidence: 99%
See 2 more Smart Citations
“…Since fatty acid profile analysis has played a central role in the pioneering taxonomic studies of the family Sphingomonadaceae (Busse et al, 1999;Takeuchi et al, 2001;Yabuuchi et al, 2002), besides the most closely related type strains shown in Table 1, all type species of closely related genera were involved in our comparative analysis (Table 2). In members of the family Sphingomonadaceae, C 18 : 1 v7c is the characteristic predominant fatty acid and the presence of 2-hydroxy fatty acids, mainly C 14 : 0 2-OH, is common, while C 17 : 1 v6c is usually present in lower amounts or is even absent (Busse et al, 1999;Takeuchi et al, 2001;Maruyama et al, 2006;Huang et al, 2009;Chen et al, 2010;Liang & Lloyd-Jones, 2010;Kämpfer et al, 2012;Uchida et al, 2012). This latter compound was found in high amounts in ERB1-3 T (29.2 %) compared with the most closely related type strains, and in ERB1-3 T , C 15 : 0 2-OH was another characteristic hydroxy fatty acid (representing .5 %).…”
Section: Cells Of Strain Erb1-3mentioning
confidence: 99%
“…Later, this genus was subdivided into four genera, Sphingomonas sensu stricto, Sphingobium, Novosphingobium and Sphingopyxis (Takeuchi et al, 2001), and in recent years, several additional new genera have been described and assigned to the family Sphingomonadaceae (e.g. Parasphingopyxis, Sphingosinicella, Sphingomicrobium and Stakelama; Maruyama et al, 2006;Chen et al, 2010;Kämpfer et al, 2012;Uchida et al, 2012). Sphingomonads are widely distributed in nature and have been isolated from different aqueous and terrestrial habitats as well as from clinical specimens (Balkwill et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…, Blastomonas (Sly & Cahill, 1997), Sandaracinobacter (Yurkov et al, 1997), Sphingosinicella (Maruyama et al, 2006), Sandarakinorhabdus (Gich & Overmann, 2006), Stakelama (Chen et al, 2010), Parasphingopyxis (Uchida et al, 2012), Sphingomicrobium (Kämpfer et al, 2012), Sphingorhabdus (Jogler et al, 2013) Hephaestia (Felföldi et al, 2014, Polymorphobacter (Fukuda et al, 2014) and Rhizorhabdus and Rhizorhapis (Francis et al, 2014). These members of the family Sphingomonadaceae share several phenotypic features, such as a polar lipid pattern containing sphingoglycolipids, the presence of Q-10 as their predominant respiratory quinone (Balkwill et al, 2006;Yabuuchi et al, 1990), a fatty acid profile containing C 14 : 0 2-OH fatty acid and a polyamine pattern with either spermidine or homospermidine as the major component.…”
mentioning
confidence: 99%
“…Yabuuchi et al (2002) and Yabuuchi & Kosako (2005) continued to use the genus name Sphingomonas, since the new combinations created by Takeuchi et al (2001) were also homotypic synonyms of species names within the genus Sphingomonas. Recently, three additional genera were classified within the family Sphingomonadaceae, namely Sphingosinicella (Maruyama et al, 2006), Stakelama (Chen et al, 2010) and Sphingomicrobium (Kämpfer et al, 2012). It should be noted, however, that Takeuchi et al (2001) did not alter the nomenclature of Rhizomonas suberifaciens van Bruggen et al 1990, indicating that they considered this species to be a member of a separate genus.…”
mentioning
confidence: 99%